Síndrome de Bouveret. A propósito de un caso. - Salazar Ray, Martín; Salazar Eduardo, Angel (Revista Médica Herediana, 2013)
A case of a 74 years old patient with duodenal gallstone ileus (Bouveret’syndrome) who had some uncommon aspects for this entity as to be of male sex, an abrupt onset of an upper intestinal obstruction with upper digestive bleeding and without antecedents of previous biliary disease, in presented. The surgical treatment was needed and consisted of a longitudinal duodenotomy, stone removal and transverse suture. The cholecystectomy and repair of the biliary fistula was deferred to be performed in an elective form. The patient was discharged on the seventh post operatory day in good condition.